Deletion of AMPKα1 attenuates the anticontractile effect of perivascular adipose tissue (PVAT) and reduces adiponectin release - Almabrouk, Tarek A M (Br J Pharmacol, 2016)
BACKGROUND AND PURPOSE: Perivascular adipose tissue (PVAT) surrounds most blood vessels and secretes numerous active substances, including adiponectin, which produce a net anticontractile effect in healthy individuals. AMPK is a key mediator of cellular energy balance and may mediate the vascular effects of adiponectin. In this study, we investigated the role of AMPK within PVAT in mediating the anticontractile effect of PVAT. EXPERIMENTAL APPROACH: Endothelium‐denuded aortic rings from wild‐type (WT; Sv129) and α(1)AMPK knockout (KO) mice were mounted on a wire myograph. Dose–response curves to the AMPK‐independent vasodilator cromakalim were studied in vessels with and without PVAT, and effect of pre‐incubation with conditioned media and adiponectin on relaxation was also studied. The effect of AMPKα1 KO on the secretory profile of PVAT was assessed by elisa. KEY RESULTS: Thoracic aortic PVAT from KO mice was morphologically indistinct from that of WT and primarily composed of brown adipose tissue. PVAT augmented relaxation to cromakalim in WT but not KO aortic rings. Addition of WT PVAT augmented relaxation in KO aortic rings but KO PVAT had no effect in WT rings. PVAT from KO mice secreted significantly less adiponectin and addition of adiponectin to either KO or WT aortic rings without PVAT augmented relaxation to cromakalim. An adiponectin blocking peptide significantly attenuated relaxation in WT rings with PVAT but not in KO rings. CONCLUSIONS AND IMPLICATIONS: AMPKα1 has a critical role in maintaining the anticontractile actions of PVAT; an effect independent of the endothelium but likely mediated through altered adiponectin secretion or sensitivity. LINKED ARTICLES: This article is part of a themed section on Molecular Mechanisms Regulating Perivascular Adipose Tissue – Potential Pharmacological Targets? To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.20/issuetoc